ESP Coursebook Evaluation: Students’ Perception on Activities and Tasks - Intan Satriani; Setya Resmini (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2021)
In teaching and learning process, teachers without preparation and materials in teaching like chefs without cooking ingredients. It can be assumed that preparing the activity and materials is important for the teachers before they deliver the lesson. On the point of that, this research is aimed at evaluating a coursebook in English for Specific Purposes (ESP) subject. It investigates students’ responses towards ESP coursebook written by Hutchinson and Waters (1987) entitled English for Specific Purposes. The evaluation format used in this research is adopted from Al-Sowat (2012). Limitation of this research is on choosing only one area as the focus of evaluation. There are activities and tasks. The participants involved in this research were university students. The data were collected by distributing questionnaire to the participants using google form. Descriptive qualitative was used to analyze and present the data. The results showed that the coursebook has strength. Students do not feel bored, also those activities can make students more creative and active in the classroom. This research suggests further research to develop an appropriate coursebook for English for Specific Purposes subject.